Letter - Gibbs, C. C. S.
1938-08-01 038-0124-002 GAYHURST SCHOOL, GERRARD'S CROSS, BUCKINGHAMSHIRE, TELEPHONE 2690. 1.8.38 Dear Sir Mr Pole has allowed me to mention his name in connection with this letter. I am anxious to receive particulars of camps etc for Basque or other refugee children with a view to finding if any require the services of an exceptionally suitable married couple - educated people who have had misfortunes and recently lost an only child. I shall be grateful if you can give 292/946/38/124(II)